Permata Di Hujung Muara 3°32'26.7"N 103°25'58. 1" E : UMP Pekan. Rakaman Peristiwa - Wan Helmy Zain, author 637472; Asraf Ahmad, author 637473; Saiful Bahari Ahmad Bakarim, editor 637474; Noor Azhar Abd. Rasid, photographer 637475; Khairu Aidilnishah Rizan Jalal, photographer 637476; Muhammad Naufal Samsudin, photographer 637477; Universiti Malaysia Pahang 556895 (Pekan, Pahang :, 2016)
Rohana Abdul Rahim